Factors Contributing to the Emergence of Escherichia coli O157 in Africa - Paul Effler; Margaretha Isaäcson; Lorraine Arntzen; Rosemary Heenan; Paul Canter; Timothy Barrett; Lisa Lee; Clifford Mambo; William Levine; Akbar Zaidi; Patricia M. Griffin (Emerging Infectious Diseases, 2001)
In 1992, a large outbreak of bloody diarrhea caused by Escherichia coli O157 infections occurred in southern Africa. In Swaziland, 40,912 physician visits for diarrhea in persons ages >5 years were reported during October through November 1992. This was a sevenfold increase over the same period during 1990-91. The attack rate was 42% among 778 residents we surveyed. Female gender and consuming beef and untreated water were significant risks for illness. E. coli O157:NM was recovered from seven affected foci in Swaziland and South Africa; 27 of 31 patient and environmental isolates had indistinguishable pulsed-field gel electrophoresis patterns. Compared with previous years, a fivefold increase in cattle deaths occurred in October 1992. The first heavy rains fell that same month (36 mm), following 3 months of drought. Drought, carriage of E. coli O157 by cattle, and heavy rains with contamination of surface water appear to be important factors contributing to this outbreak.